Echographic signal processing - HERMENT, A.; PERONNEAU, P.; DEMOMENT, G. (Archives of Acoustics, 1984)
The information received from the insonified tissues is strongly filtered by the echograph. The acoustic probe technology and the simplified processing of the echoes are mainly responsible for this loss of information.Two deconvolution methods have been designed to correct partly the echograph characteristics. The first one, which is a suboptimal Kalman filter, is easy to implement and offers short calculation time. It is consequently well dedicated to quasi real time imaging. The second one is slower but extracts from the processed signal some geometric information on the medium interfaces. This information may be used to obtain a more precise estimation of the coefficients of reflexion in the medium and thus to characterize the tissues by their acoustic impedance.The ability of the methods to process real echographic signals is demonstrated on the rabbit eye and the human humeral artery.